Flora Malesiana. Series I - Seed Plants, Volume 14. Myristicaceae Compiled and published under the auspices of Foundation Flora Malesiana - Willem de Wilde (Flora Malesiana. Series, 2014)
Contains the taxonomic revision of one family, Myristicaceae, for Malesia, i.e. the area covering the countries Indonesia, Malaysia, Brunei Darussalam, Singapore, the Philippines, and Papua New Guinea.